A Rare Case of an Aggressive Clear Cell Variant of Calcifying Epithelial Odontogenic Tumor in the Posterior Maxilla. (August 2020) - de Arruda, José Alcides Almeida; Arantes, Diego Antônio Costa; Schuch, Lauren Frenzel; Mosconi, Carla; Abreu, Lucas Guimarães; de Andrade, Bruno Augusto Benevenuto; Romañach, Mario José; Mesquita, Ricardo Alves; Silva, Tarcília Aparecida; Batista, Aline Carvalho; Mendonça, Elismauro Franscisco
A clear cell variant of calcifying epithelial odontogenic tumor is a rare benign odontogenic neoplasm, accounting for 33 cases described in the literature. In this article, we report a challenging example of clear cell variant of calcifying epithelial odontogenic tumor of the posterior maxilla in a 45-year-old female patient showing locally aggressive growth and recurrence. Microscopically, islands of polyhedral cells containing abundant cytoplasm, well-developed intercellular bridges blended with clear cells were observed. The nuclei were frequently pleomorphic and permeated by hyaline calcified material. Immunohistochemistry revealed positivity for pan-cytokeratin (AE1/AE3), cytokeratins (CK-14 and CK-19), Bcl-2, p53, and p63. The Ki-67 proliferative index was 10%. As odontogenic tumors are rare, when a significant clear cell component is observed, the differential diagnosis with other lesions of the jaws with similar morphology, including other odontogenic tumors with prominent clear cell component, clear cell odontogenic carcinomas, and metastatic tumors, is difficult.